2023
DOI: 10.1111/cge.14420
|View full text |Cite
|
Sign up to set email alerts
|

A X‐linked nonsense APOO/MIC26 variant causes a lethal mitochondrial disease with progeria‐like phenotypes

Leon Peifer‐Weiß,
Mazen Kurban,
Céline David
et al.

Abstract: APOO/MIC26 is a subunit of the MICOS complex required for mitochondrial cristae morphology and function. Here, we report a novel variant of the APOO/MIC26 gene that causes a severe mitochondrial disease with overall progeria‐like phenotypes in two patients. Both patients developed partial agenesis of the corpus callosum, bilateral congenital cataract, hypothyroidism, and severe immune deficiencies. The patients died at an early age of 12 or 18 months. Exome sequencing revealed a mutation (NM_024122.5): c.532G&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…To understand these metabolic changes and their dependency on mitochondrial ultrastructure and function is of high medical relevance as nutrient-overload is known to cause obesity and T2DM in humans. In fact, MIC26 mutations are also associated with mitochondrial myopathy, lactic acidosis (Beninca et al, 2021) as well as lethality and progeria-like phenotypes (Peifer-Weiß et al, 2023). We showed that cellular fatty acid synthesis, cholesterol biosynthesis and LD formation is promoted by MIC26 under high glucose conditions but that these pathways are conversely inhibited by MIC26 under normal glucose concentrations (Fig 7H).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…To understand these metabolic changes and their dependency on mitochondrial ultrastructure and function is of high medical relevance as nutrient-overload is known to cause obesity and T2DM in humans. In fact, MIC26 mutations are also associated with mitochondrial myopathy, lactic acidosis (Beninca et al, 2021) as well as lethality and progeria-like phenotypes (Peifer-Weiß et al, 2023). We showed that cellular fatty acid synthesis, cholesterol biosynthesis and LD formation is promoted by MIC26 under high glucose conditions but that these pathways are conversely inhibited by MIC26 under normal glucose concentrations (Fig 7H).…”
Section: Discussionmentioning
confidence: 75%
“…Mutations in MIC26 were reported to result in mitochondrial myopathy, lactic acidosis and cognition defects (Beninca et al, 2021) as well as a lethal progeria-like phenotype (Peifer-Weiß et al, 2023). Interestingly, there is an intricate connection between MIC26 and metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…We show here that MIC26 is a novel substrate of YME1L which is specifically regulated by the SLP2-YME1L axis. Recently, we have reported a pathological mutation in MIC26 that causes lethal mitochondrial disease with progeria-like phenotypes (Peifer-Weiß et al, 2023). This MIC26 variant with loss of the last twenty amino acids at the C-terminus is prone to faster degradation such that the mutant behaves like a loss-of-function variant.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, no curative treatment is known. Mutations of MIC60, MIC26 and MIC13 have been found in several severe human diseases (Beninca, Zanette et al, 2021a, Guarani, Jardel et al, 2016, Peifer-Weiß, Kurban et al, 2023, Russell, Whaley et al, 2019, Tsai, Lin et al, 2018, Zeharia, Friedman et al, 2016. The question remains how cristae and CJs are formed and maintained during the healthy or pathological conditions and how does specific MICOS subunit contribute to these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Both MICOS subcomplexes are necessary for the formation of crista junctions and their physical coupling is largely mediated by Mic12/QIL1 (Guarani et al , 2015; Zerbes et al , 2016). MICOS deficiency causes the loss of crista junctions and the detachment of cristae from the inner boundary membrane, and loss of function mutations in human patients cause severe mitochondrial pathologies, including a fatal encephalopathy (John et al , 2005; Rabl et al , 2009; Mun et al , 2010; Harner et al , 2011; Hoppins et al , 2011; Malsburg et al , 2011; Guarani et al , 2016; Zeharia et al , 2016; Benincá et al , 2021; Peifer-Weiß et al , 2023).…”
Section: Introductionmentioning
confidence: 99%